Effects of photoperiod on nutrient removal, biomass production, and algal-bacterial population dynamics in lab-scale photobioreactors treating municipal wastewater. (1st January 2015) - Lee, Chang Soo; Lee, Sang-Ah; Ko, So-Ra; Oh, Hee-Mock; Ahn, Chi-Yong
Abstract: Effects of photoperiod were investigated in lab-scale photobioreactors containing algal-bacterial consortia to reduce organic nutrients from municipal wastewater. Under three photoperiod conditions (12 h:12 h, 36 h:12 h, and 60 h:12 h dark–light cycles), nutrient removals and biomass productions were measured along with monitoring microbial population dynamics. After a batch operation for 12 days, 59–80% carbon, 35–88% nitrogen, and 43–89% phosphorus were removed from influents, respectively. In this study, carbon removal was related positively to the length of dark cycles, while nitrogen and phosphorus removals inversely. On the contrast, the highest microbial biomass in terms of chlorophyll a, dry cell weight, and algal/bacterial rRNA gene markers was produced under the 12 h:12 h dark–light cycle among the three photoperiods. The results showed 1) simultaneous growths between algae and bacteria in the microbial consortia and 2) efficient nitrogen and phosphorus removals along with high microbial biomass production under prolonged light conditions. Statistical analyses indicated that carbon removal was significantly related to the ratio of bacteria to algae in the microbial consortia along with prolonged dark conditions ( p  < 0.05). In addition, the ratio of nitrogen removal to phosphorus removal decreased significantly under prolonged dark conditions ( p  < 0.001). These results indicated that the photoperiod condition has remarkable impacts on adjusting nutrient removal, producing microbial biomass, and altering algal-bacterial population dynamics. Therefore, the control of photoperiod was suggested as an important operating parameter in the algal wastewater treatment. Graphical abstract: Highlights: Up to 80–89% of organic nutrients were removed from wastewater in photobioreactor. Microbial biomass of algal-bacterial consortia ranged up to 0.7 g/L after 6 days. Bacteria/algae ratio correlated positively with dark/light ratio in photoperiod. Prolonged dark cycle fosters sCOD removal by increasing bacteria/algae ratio. Prolonged light cycle facilitates TDN and TDP removals by increasing total biomass.